COMMUNITIES’ PERCEPTIONS OF LAND DEGRADATION: A CASE STUDY IN THE SAVANNA BELT OF THE WHITE VOLTA BASIN - Baatuuwie, N. B.; Le, Q. B.; Agyare, A. W.; Forkuo, K. E. (UDS International Journal of Development, 2017)
This study explores the views and perceptions of land users on land degradation and the possible mitigation measures within the White Volta Basin in Ghana. Twenty-three (23) communities were selected within the catchment to evaluate their perceptions of land degradation indicators, socio-ecological drivers and possible mitigation measures to combat the degradation in the basin. Group discussion and field observation with local people in the communities were employed to gather data on direct and indirect causes of land degradation as well as possible mitigation measures. Data collected were analyzed using Statistical Package for Social Sciences (SPSS) software. Descriptive statistical methods were used to explore the data and Relative Importance Index (RII) of the degradation indicators, direct and indirect causes was computed in order to prioritize these issues in the study area. Eight indicators were used by the farmers and other land users to identify degraded land in the area. These indicators were readily observable and were similar in characteristics to those scientists commonly use. Formation of rills/gullies, change in soil colour and increased in barren land area were the most common observable indicators used in identifying degraded land in the study area. Poor soil management and deforestation are perceived to be the most important causes of land degradation in the basin. Increasing human population and poverty were perceived to be the indirect drivers responsible for the degradation. Key possible mitigation measures to reduce the degradation in the basin include: controlled bush burning, minimum tillage and stone bunds. Keywords: Land degradation, Indicators, White Volta Basin, PerceptionÂ